PENGARUH RASIO LEVERAGE, RASIO OPERATING CAPACITY, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP FINANCIAL DISTRESS PADA MASA PANDEMIC COVID 19 - Marli Marli; Renna Li’is Raaqi Nuurika; Dwi Danesty Deccasari (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This research aims to analyze the effect of leverage, operating capacity, managerial ownership, institutional ownership on financial distress. The leverage variable is measured by the DER and DAR indicator. The operating capacity variable is measured by the TATO indicator. The managerial ownership variable is measured by calculation formula managerial ownership. The institutional ownership variable is measured by calculation formula institutional ownership. The financial distress variable by the Z-Score indicator. The research object used is the food and beverages sub sector manufacturing companies and chemicals listed on the Indonesia Stock Exchange during the covid 19 pandemic in 2020 quarter 1 to quarter 4. This research uses purposive sampling technique to determine the research sample. There were 16 companies that met the sample criteria as determined. This study uses partial least square (PLS) analysis to analyze the data. The result of this study Leverage has a significant negative effect on financial distress. Operating capacity has a significant positive effect on financial distress. Managerial ownership has a significant negative effect on financial distress. Institutional ownership has a significant negative effect on financial distress.